1988
DOI: 10.1210/jcem-67-2-334
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Human Uterine Estrogen and Progesterone Receptors Throughout the Menstrual Cycle*

Abstract: Estrogen receptors (ER) and progesterone receptors (PgR) were studied immunohistochemically using specific antireceptor monoclonal antibodies in uterine tissue samples from 33 women in various stages of the menstrual cycle. Immunohistochemical localization was quantified as to intensity of staining and tissue distribution in glandular epithelium, stroma, and myometrium, and the results were compared with those of standard ligand binding assays. In all samples ER and PgR localized within the nuclei of target ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
261
6
10

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(323 citation statements)
references
References 24 publications
43
261
6
10
Order By: Relevance
“…The decrease in OR positive cases in the second half of the menstrual cycle is the same as the endometrium (Press et al, 1984;Lessey et al, 1988) and is consistent with the accepted dogma of OR down-regulation as a consequence of progesterone action. The present study further supports this from observations in OC cycle, where there is a striking decrease in detection with use, presumably on account of downregulation by exogenous progestins.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The decrease in OR positive cases in the second half of the menstrual cycle is the same as the endometrium (Press et al, 1984;Lessey et al, 1988) and is consistent with the accepted dogma of OR down-regulation as a consequence of progesterone action. The present study further supports this from observations in OC cycle, where there is a striking decrease in detection with use, presumably on account of downregulation by exogenous progestins.…”
Section: Discussionsupporting
confidence: 85%
“…In part, the controversy reflects the difference in data derived from tissues obtained ex vivo from those derived from cell culture and from xenografts in nude mice, but another factor has been the assumption of similarity in the steroidal regulation of breast and endometrial epithelia. While a clear picture of oestrogen receptor and progesterone receptor regulation exists for endometrium (Lessey et al, 1988), the same is not true for breast. Oestrogen and progesterone receptors (OR and PR) are both present in normal human breast epithelium (Petersen et al, 1987;Jacquemier et al, 1990;Joyeux et al, 1990;Williams et al, 1991) but with lack of agreement between authors as to differences across the cycle or consistency within it.…”
mentioning
confidence: 99%
“…This variability is related to the known effects of estrogen and progesterone on steroid hormone receptor expression. 22 Although steroids control endometrial function, paracrine and autocrine growth factor/cytokine signals are now viewed as key mediators of reproductive function. It has been suggested that neovascularization in normal endometrial tissue is indirectly modulated by ovarian steroids via the production of locally active angiogenic factors, such as vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial glandular growth is estrogen dependent, yet glandular estrogen receptors are downregulated and undetectable at the time of implantation. 21 Inductive stromal-epithelial interactions regulate endometrial growth and differentiation leading to endometrial receptivity. 22 Estrogen presumably stimulates endometrial glandular development via a paracrine mechanism acting through the stromal estrogen receptor.…”
Section: Discussionmentioning
confidence: 99%